(untitled) (Environment & Health, 2020)
Оbjective: We improved the hygienic criteria to ensure optimal conditions, training, and preservation of the health of primary school age pupils, which are common for the assessment of architectural-and-planning decisions of urban and rural secondary schools in accord with modern town-planning and sanitary legislation. Materials and methods: We applied bibliosemantic, analytical methods, method of sanitary-and-epidemiological examination of construction projects, sociological, instrumental and medico-statistical ones using StatSoft STATISTICA (v.5.5) application packages, Excel. Results: The exceeding 1.8-2.3 times the number of the actual studies that do not meet the standards for natural light and noise in urban secondary schools in comparison with the rural secondary schools, is due to the dense town-planning situation. The results of the survey of the parents of the pupils in grades 1-4 on the impact of dense school conditions of secondary schools on the indirect parameters of architectural-and-planning decisions showed that in case of insufficient space of the school room, a poor well-being was registered in 26.3% of pupils (rS